Assessing the whole-match and worst-case scenario locomotor demands of international women's rugby union match-play. Issue 6 (June 2020) - Sheppy, Emily; Hills, Samuel P.; Russell, Mark; Chambers, Ryan; Cunningham, Dan J.; Shearer, David; Heffernan, Shane; Waldron, Mark; McNarry, Melitta; Kilduff, Liam P.
Abstract: Objectives: To profile the distances covered during international women's rugby union match-play and assess the duration-specific worst-case scenario locomotor demands over 60-s to 600-s epochs, whilst comparing the values determined by fixed epoch (FIXED) versus rolling average (ROLL) methods of worst-case scenario estimation and assessing positional influences. Design: Descriptive, observational. Methods: Twenty-nine international women's rugby union players wore 10 Hz microelectromechanical systems during eight international matches (110 observations). Total, and per-half, distances were recorded, whilst relative total and high-speed (>4.4 m s −1 ) distances were averaged using FIXED and ROLL methods over 60–600-s. Linear mixed models compared distances covered between match halves, assessed FIXED versus ROLL, and examined the influence of playing position. Results: Players covered ∼5.8 km match −1, with reduced distances in the second- versus first-half (p < 0.001). For worst-case scenario total (∼8–25%) and high-speed (∼10–26%) distance, FIXED underestimated ROLL. In ROLL, worst-case scenario relative total and high-speed distances reduced from ∼144−161 m min −1 and ∼30−69 m min −1 over 60-s, to ∼80 89 m min −1 and ∼5 16 m min −1 in the 600-s epoch, respectively. Forwards performed less high-speed running over all epochs and covered less total distance during epochs of 60-s, 180-s, 420-s and 480-s, compared with backs. Front row players typically returned the lowest locomotor demands. Conclusions: This is the first study reporting the positional and worst-case scenario demands of international women's rugby union, and indicates an underestimation in FIXED versus ROLL over 60-s to 600-s epochs. Knowledge of the most demanding periods of women's rugby union match-play facilitates training specificity by enabling sessions to be tailored to such demands.